Memory Transmission: Political Trauma in the Short Story 'The Last Night' by Leila S. Chudori - Attila P. M, Archimedes; Fadilah, Yuniardi (Proceedings International Conference of Culture and Sustainable Development; Vol 2 (2024): PROCEEDINGS ICOCAS, 2024)
The short story â€œThe Last Nightâ€ by Leila S. Chudori shows how student activists were treated badly during Indonesiaâ€™s New Order era. It also shows how political trauma is passed on from one generation to the next. This study looks at how collective memory and trauma are passed down from those who experienced them firsthand to subsequent generations, using Marianne Hirschâ€™s concept of postmemory. This research is important because it shows how historical trauma affects how younger people see political events and authority. The research uses qualitative descriptive methods to look at the conversations in the short story and identify and analyse the factors involved in memory transmission. The research found that both familial and affiliative postmemory transmission play a part in how political trauma is inherited. The story shows how the younger generationâ€™s views and feelings are influenced by the experiences and actions of those who lived through the traumatic events. This study helps us to understand postmemory and how it affects how future generations see political history.
Keywords: Postmemory, political trauma, memory transmission, New Order, activist